2020
DOI: 10.1002/ehf2.13022
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for myocardial injury in patients with coronavirus disease 2019 in China

Abstract: Aims In patients with coronavirus disease 2019 (COVID‐19), the involvement of the cardiovascular system significantly relates to poor prognosis. However, the risk factors for acute myocardial injury have not been sufficiently studied. Thus, we aimed to determine the characteristics of myocardial injury and define the association between routine blood markers and cardiac troponin I, in order to perform a predictive model. Methods and results This retrospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…What's more, our study also identified that elevated LDH, the presence of echocardiographic abnormalities, the presence of cardiac abnormalities at admission, and the severity of COVID-19 were risk factors for cardiac sequelae in COVID-19 survivors in the late convalescent stage. This was consistent with previous study that focused on risk stratification of cardiac involvement in COVID-19 patients during hospitalization [10] . This implies that physicians should pay more attention to these high risk patients during follow-up, and CMR could be performed to screen out cardiovascular involvement in late convalescence.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…What's more, our study also identified that elevated LDH, the presence of echocardiographic abnormalities, the presence of cardiac abnormalities at admission, and the severity of COVID-19 were risk factors for cardiac sequelae in COVID-19 survivors in the late convalescent stage. This was consistent with previous study that focused on risk stratification of cardiac involvement in COVID-19 patients during hospitalization [10] . This implies that physicians should pay more attention to these high risk patients during follow-up, and CMR could be performed to screen out cardiovascular involvement in late convalescence.…”
supporting
confidence: 93%
“…This was consistent with previous study that focused on risk stratification of cardiac involvement in COVID-19 patients during hospitalization. 10 This implies that physicians should pay more attention to these high risk patients during follow-up, and CMR could be performed to screen out cardiovascular involvement in late convalescence.…”
mentioning
confidence: 99%
“…In addition, a high prevalence of pre-existing cardiovascular morbidities, including hypertension, and coronary artery diseases, has been detected among patients with severe SARS-CoV-2 ( 1 , 149 , 156 ). In COVID-19 patients, the highest mortality rates were also observed in case of pre-existing cardiovascular disease and elevated cardiac troponin levels ( 137 , 157 ). Furthermore, patients with higher troponin levels had also increased markers of inflammation, including C-reactive protein, interleukin (IL)-6, ferritin, lactate dehydrogenase (LDH), high neutrophil count, and high amino-terminal pro-B–type natriuretic peptide ( 158 ).…”
Section: Sars-cov-2 Clinical Implication and Potential Mutual Interacmentioning
confidence: 99%
“…Since the first Chinese reports, a high incidence of cardiac injury, defined as the presence of elevated troponin (Tn) levels above the 99th percentile of the reference interval, was found in COVID-19 patients. The prevalence of cardiac injury ranges from 12% in unselected COVID-19 cases up to 41% in critically ill patients and patients with pre-existing cardiovascular diseases with a further rise to 75.8% in nonsurvivors (Table 3) (14,17,18,24,25,38,39,(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82). The presence of elevated Tn levels is associated with abnormal laboratory findings (including white blood cells count, neutrophil and lymphocyte count, C-reactive protein, procalcitonin, Nterminal pro-B-type natriuretic peptide, D-dimer, transaminases, lactate dehydrogenase, total bilirubin, albumin, prothrombin time, and cytokines) (18) and a higher grade of pulmonary involvement in radiographic findings, suggesting an important multiorgan involvement (21,38,73).…”
Section: Subclinical Acute Myocardial Injury In Covid-19mentioning
confidence: 99%
“…The presence of cardiac injury in COVID-19 is associated with more severe manifestations, complications, and adverse prognosis (14,17,18,24,25,38,39,(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82). Data about the association between cardiac injury and mortality are summarized in Table 3.…”
Section: Sars and Middle East Respiratory Syndrome (Mers) (3)mentioning
confidence: 99%